Regulation of Thalamic Development by Sonic Hedgehog - Epstein, Douglas J. (Frontiers in Neuroscience, 2012)
The thalamus is strategically positioned within the caudal diencephalic area of the forebrain, between the mesencephalon and telencephalon. This location is important for unique aspects of thalamic function, to process and relay sensory and motor information to and from the cerebral cortex. How the thalamus comes to reside within this region of the central nervous system has been the subject of much investigation. Extracellular signals secreted from key locations both extrinsic and intrinsic to the thalamic primordium have recently been identified and shown to play important roles in the growth, regionalization, and specification of thalamic progenitors. One factor in particular, the secreted morphogen Sonic hedgehog (Shh), has been implicated in spatiotemporal and threshold models of thalamic development that differ from other areas of the CNS due, in large part, to its expression within two signaling centers, the basal plate and the zona limitans intrathalamica, a dorsally projecting spike that separates the thalamus from the subthalamic region. Shh signaling from these dual sources exhibit unique and overlapping functions in the control of thalamic progenitor identity and nuclei specification. This review will highlight recent advances in our understanding of Shh function during thalamic development, revealing similarities, and differences that exist between species.